1984
DOI: 10.1111/j.1600-0447.1984.tb02527.x
|View full text |Cite
|
Sign up to set email alerts
|

Theophylline precipitated alterations of lithium clearance

Abstract: The effect of steady state therapeutic theophylline serum levels on lithium clearance was investigated. A significant increase in lithium clearance occurred with the administration of theophylline. Despite considerable intersubject variability, a direct lithium clearance estimation method demonstrated a mean increase of 30% with the addition of theophylline. The concomitant use of lithium and theophylline potentially may alter lithium levels sufficiently to result in manic or depressive relapses in patients re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…In this context it is important to note that methylxanthine drugs caffeine and theophylline that increase NHA2 levels are well known to promote Li + clearance via kidney. These drugs enhance renal salt and water transport and are contraindicated for Li + therapy (48,49). Using ratiometric Fura 2 Ca 2+ imaging, we first confirmed significant increase in cytoplasmic Ca 2+ with caffeine and theophylline treatment in MDCK cells ( Fig.…”
Section: Potential Modulation Of Kidney Function By Drug and Hormonalmentioning
confidence: 59%
See 1 more Smart Citation
“…In this context it is important to note that methylxanthine drugs caffeine and theophylline that increase NHA2 levels are well known to promote Li + clearance via kidney. These drugs enhance renal salt and water transport and are contraindicated for Li + therapy (48,49). Using ratiometric Fura 2 Ca 2+ imaging, we first confirmed significant increase in cytoplasmic Ca 2+ with caffeine and theophylline treatment in MDCK cells ( Fig.…”
Section: Potential Modulation Of Kidney Function By Drug and Hormonalmentioning
confidence: 59%
“…Caffeine is also thought to promote cyst development in PKD patients (43). Furthermore, caffeine and theophylline are well known to promote clearance of lithium through kidney (48,49). Given our previous findings that NHA2 is an important cellular lithium efflux transporter (17)…”
Section: Discussionmentioning
confidence: 91%
“…Besides use and start of potentially interacting co‐medication, the withdrawal of these agents could also influence lithium serum levels. However, it has been reported that withdrawal is more likely to result in a decrease (12–38) rather than in an increase in lithium serum level. As our focus is on the appearance of elevated lithium serum levels, data on withdrawal of potentially interacting drugs was of lesser importance to this report.…”
Section: Discussionmentioning
confidence: 99%
“…In ten healthy subjects with normal renal function administered lithium carbonate 900mg daily for 7 days, the addition of theophylline to achieve steadystate plasma concentrations of between 5 and 12mg/1 significantly (P < 0.05) increased the renal clearance of lithium by an average of 42% from 18.3 ± 7.0 to 26.1 ± 11.5mllmin and shortened the half-life from 28.1 ± 7.5 to 21.8 ± 6.6h (PERRY et al 1984). There was also a significant decrease in serum lithium concentrations by an average of 30%.…”
Section: A) Theophyllinementioning
confidence: 99%